SUPPLEMENT TO THE GENUS CAREX IN MALAYSIA - E. NELMES (Reinwardtia, 1954)
This Supplement to the author's monograph "The genus Carex in Malaysia"enumerates several additional collections. Moreover, a revised description of Carex pycnothyrsos Kukenth. is given, while C. teinogyna Boott, C. formosensis Lev. & Van. (?), and C. gajonum Nelmes, three species not dealt with in the main work, are fully treated.